PENGARUH VARIABEL EKONOMI MAKRO PADA RETURN SAHAM LQ45 DI BURSA EFEK INDONESIA - Mirayanti, Ni Made; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2017)
The purpose of this study is to determine the influence of macroeconomic variables on stock return of the LQ45 Index members in the Indonesia Stock Exchange. The sample of this study is compan is listed in the LQ45 Index for six periods from 201 3 to 2016 . Initially , the sample had 270 observations. However, four of those observations were identified as outliers and therefore were dropped from the sample. Data were analyzed by multiple linear regression. The results of the analysis show that inflation positively affect stock returns of the companies listed in the LQ45 Index in Indonesia Stock Exchange. Interest rate and exchange rate of Rupiah have negative effects on the stock return of the companies listed in the LQ45 Index in Indonesia Stock Exchange. Gross domestic product and money supply have no effect on the stock return of the companies listed in the LQ45 Index in Indonesia Stock Exchange. In accordance with the results of the data analysis, stock investors are advised to consider the inflation rate, exchange rate, and interest rate in making investment decision in the Indonesia Stock Exchange.